Taklif Islam dalam Mencegah LGBT - Muhayati, Siti (Ridwan Institute, 2021)
Taklif Islam is a charge (Risalah Muslim, No year) gives the face of the living during and the people of the Prophet Muhammad see which orders must be obeyed, or advice, or advice or advice can not or choose that can not be on mandatory, sunnah, haram and makruh. The purpose of this study is anything to know the taklif Islam as a deterrent to LGBT behavior that is under the guise of the authors of Islamic religious experts (scholars). LGBT behavior appears no situation is still in the pandemic covid 19 and conditions in the injury of covid 19 or in the condition at home in medical personnel kesesan to obey it to be prevented from LGBT behavior. This type of research is research literature. Intrumen research itself researchers with charcoal peratnyaan guidelines for data according to the title of this study. The data source is the fruit of articles contained in various journals, magazines, blogspot, books and research reports. Analysis of the data by editing is which is the title with the title of the study, in addition the data is summarized for the group as long as the criteria of the focus of the research then the drawing of the sweepstakes. The results of his research religion, the authors of Islamic religious experts (scholars) on LGBT both related, the emergence factor, international factors, prolahnya, lgbt repentance guidance.